O macroambiente de emergência dos ecossistemas industriais: proposição de estrutura analítica e aplicação para o caso brasileiro - Marquez Júnior, Rodrigo Octávio Pereira (2014)
Given the enormous environmental devastation caused in large part by unrestricted use of natural resources, it is fundamental to develop alternative means of production, guided by efficiency and sustainability . In this scenario, emerging industrial ecosystems, characterized by being formed clusters through a network of firms linked by an ecological, social and economic logic. These clusters can be encouraged from adequate to its emergence and development environment. The research can be classified as descriptive, qualitative nature, emerged from the need to develop alternative means of production. According to the international literature review it appears that aspects related to public initiatives, laws and private initiatives are suitable to create favorable conditions for the development of this type of arrangement means product. This elements make up what, for the purposes of this research will be named the macro environment of formation of industrial ecosystems. The overall objective is to identify the variables used worldwide to study the macro environment where training initiatives of industrial ecosystems emerge, as well as analyzing the behavior of the domestic macro environment to observe it through these same variables. As a result it was found a consistent analysis model, and apply it to the Brazilian case there has been a set of policies such as the National Environmental Policy pursuing sustainable development, but for these policies are quite sparse, and the Brazil present some peculiarities, due to its historical origins, the large territory and little environmental awareness, we can not say that there are concise for industrial symbiosis stimuli.